Os limites da exclusão religiosa e racial na América Latina colonial - Puntoni, Pedro (Afro-Ásia, 2022)
Resenha de: Schwartz, Stuart. Blood and Boundaries: The Limits of Religious and Racial Exclusion in Early Modern Latin America. Waltham: Brandeis University Press, 2020. 187 p.